2015
DOI: 10.1021/acs.jafc.5b04394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extraction Conditions on the Saccharide (Neutral and Acidic) Composition of the Crude Pectic Extract from Various Agro-Industrial Residues

Abstract: The influence of different extraction methodologies was assessed on the composition of both neutral (arabinose, rhamnose, galactose) and acidic (galacturonic acid) pectic polysaccharides obtained from four agro-industrial residues, namely, berry pomace (BP), onion hulls (OH), pressed pumpkin (PP), and sugar beet pulp (SBP). For acidic pectic polysaccharides, the extraction efficiency was obtained as BP (nitric acid-assisted extraction, 2 h, 62.9%), PP (enzymatic-assisted extraction, 12 h, 75.0%), SBP (enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Pectin was extracted by the traditional acidifying method optimized by Neha Babbar et al [41] with slight modifications. The sample was mixed with deionized water (5%, w/v ) and the pH was adjusted to 1.2 with HNO 3 12 M. The suspended samples were heated at 90 °C with continuous stirring at 200 rpm for 3 h. After the reaction was completed, the resulting slurries were cooled down to 40 °C, and the pH was adjusted to 4.5 with NH 3 .H 2 O 25% and centrifuged at 2600× g at 4 °C for 10 min, to separate insoluble fiber, protein, and other non-pectin compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Pectin was extracted by the traditional acidifying method optimized by Neha Babbar et al [41] with slight modifications. The sample was mixed with deionized water (5%, w/v ) and the pH was adjusted to 1.2 with HNO 3 12 M. The suspended samples were heated at 90 °C with continuous stirring at 200 rpm for 3 h. After the reaction was completed, the resulting slurries were cooled down to 40 °C, and the pH was adjusted to 4.5 with NH 3 .H 2 O 25% and centrifuged at 2600× g at 4 °C for 10 min, to separate insoluble fiber, protein, and other non-pectin compounds.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, enzyme assisted extraction (EAE) has been widely used for the extraction of target compounds from different materials [1][2][3]. Compared with conventional methods, EAE improved the time efficiency, reduced the solvent consumption and operated at milder extraction temperature [4,5]. The positive effect of EAE is that the cell walls catalyzed by enzyme became thin and disorganized under optimum experimental conditions, then the intracellular components were released more completely, leading to the improved yield [6].…”
Section: Introductionmentioning
confidence: 99%
“…Babbar et al [14] observed that in comparison to the use of acids and chelators, enzymatic extraction is rapid and the extracts so obtained are greener and safer, which consequently find uses in pharmaceutical industry. Upon enzymatic extraction, increase in various biological activities of bioactives has also been observed.…”
Section: B) Eae Makes the Extract Innocuous And Pharmacologically Mormentioning
confidence: 99%